Konsep Eksosistem Pendidikan Merdeka: Perspektif Filosofis dan Praksis Najelaa Shihab - Indah Solekhah Candra; Masduki Asbari; Putri Ramadhani Rozikin (Journal of Information Systems and Management (JISMA), 2023)
This study aims to describe the concept of the Independent Education ecosystem in Learning from Najelaa Shihab's perspective. This study report uses a descriptive qualitative method by taking notes because the data source was obtained by listening to oral narratives from the Bukalapak Wyang YouTube channel entitled "Najelaa Shihab - Independent Education Ecosystem in Learning | BukaTalks” presented by Najelaa Shihab. The results of this study explain that the concept of independent learning according to Najelaa Shihab's view is the foundation of lifelong learning. The meaning of freedom in learning is that schools, teachers and students have freedom, such as freedom to innovate, freedom to learn independently and creatively. In this video, Najelaa opens a new perspective that freedom to learn is not something that is given but is a process that must be accelerated like the emancipation process. He explained three essential things in the practice of independent learning, namely: (a). commitment and consistency towards learning objectives, (b). achieve learning independence by taking control over the entire learning process ourselves, (c). the importance of reflection, namely reflecting on what we do and reviewing the good processes that have been carried out as educators. These three essential things are interconnected to form the character of independent learning teachers. Independent teachers are expected to be able to produce competencies that have an impact on students who are expected to foster a spirit of collaboration in the educational ecosystem and be able to build roles and career paths not only as educators in the classroom, for example being active writers who can inspire other educators. One of the tasks carried out by independent learning teachers is to fight misconceptions that exist in the world of education itself.